Olfactory tubercle stimulation alters odor preference behavior and recruits forebrain reward and motivational centers - FitzGerald, Brynn J.; Richardson, Kara; Wesson, Daniel W. (Frontiers in Behavioral Neuroscience, 2014)
Rodents show robust behavioral responses to odors, including strong preferences or aversions for certain odors. The neural mechanisms underlying the effects of odors on these behaviors in animals are not well understood. Here, we provide an initial proof-of-concept study into the role of the olfactory tubercle (OT), a structure with known anatomical connectivity with both brain reward and olfactory structures, in regulating odor-motivated behaviors. We implanted c57bl/6 male mice with an ipsilateral bipolar electrode into the OT to administer electric current and thereby yield gross activation of the OT. We confirmed that electrical stimulation of the OT was rewarding, with mice frequently self-administering stimulation on a fixed ratio schedule. In a separate experiment, mice were presented with either fox urine or peanut odors in a three-chamber preference test. In absence of OT stimulation, significant preference for the peanut odor chamber was observed which was abolished in the presence of OT stimulation. Perhaps providing a foundation for this modulation in behavior, we found that OT stimulation significantly increased the number of c-Fos positive neurons in not only the OT, but also in forebrain structures essential to motivated behaviors, including the nucleus accumbens and lateral septum. The present results support the notion that the OT is integral to the display of motivated behavior and possesses the capacity to modulate odor hedonics either by directly altering odor processing or perhaps by indirect actions on brain reward and motivation structures.